An Assessment of LAC's Vital Statistics System : The Foundation of Maternal and Infant Mortality Monitoring - Danel, Isabella; Bortman, Marcelo (World Bank, Washington, DC, 2013)
Vital records, the registration of births, deaths, marriages and divorces, and the vital statistics derived from these records serve two important purposes. Firstly, vital records are legal documents, but the focus of this review, is the role of vital records to create demographic and epidemiological statistics that are used in monitoring trends and developing health policies and programs. Vital statistics are classic public goods, and the World Bank is keenly interested in assisting countries in the Latin America region to strengthen their vital statistics systems. This assessment reviews the status and evolution of vital statistics systems in Latin America and makes recommendations for improving their coverage, quality, and timeliness. The strongest systems in the region on the measures of coverage, quality and timeliness are found in Argentina, Chile, Costa Rica, and Uruguay. This review found that countries in Latin America are well ahead of many other regions in the world in developing their vital registration systems. Yet challenges remain before these systems can support results-oriented health programs. Concerted efforts to improve these systems are likely to generate large payoffs in terms of supporting better public policies. Vital statistics should very soon replace surveys in Latin America as the most important primary source of information about births and deaths given their potential to more effectively guide policymaking and monitor results related to the maternal and infant health Millennium Development Goals (MDGs).